Contact Experiences Among Donor Conception Parties: Donor Conceived Persons, Donors, Parents and Same-donor Siblings – A Mixed Methods Systematic Review - Hall, K; Goedeke, S; van Kessel, K (Informa UK Limited, 2026)
As more jurisdictions allow donor-conceived persons (DCPs) access to their genetic information and direct-to-consumer DNA testing becomes increasingly popular, contact between those involved in donor conception, including DCPs, donors, parents and same-donor families, has grown. This mixed methods systematic review (MSSR) collates and examines research on how contact is experienced by these groups in the context of donation from donors previously unknown to recipients prior to donation. A bibliographic search of English-language, peer-reviewed studies was conducted following PRISMA 2020 guidelines across several databases, including CINAHL, JSTOR, MEDLINE, PsycINFO, PubMed, Scopus, Ovid Emcare and Google Scholar. Studies were included if they used empirical methods (quantitative, qualitative, or mixed) and involved participants with post-birth contact experiences following donation to recipients from donors not known to recipients prior to donation. These could include clinic-recruited donors (both anonymous/non-identified and identity-release) and donors recruited by recipients, such as through online platforms. From 1,397 initial records, 231 were full text screened. 57 studies meeting inclusion criteria and varying in methodology and sample size were assessed using the Joanna Briggs Institute (JBI) Checklist for Systematic Reviews and Research Synthesis. Findings were synthesised by stakeholder groups (DCPs, donors, parents), examining the form, frequency and experience of contact, as well as influencing factors. Contact ranged from occasional online interactions to regular in-person meetings, with experiences generally positive across all groups. Variations in experience were associated with attitudes towards and expectations of contact, and the size of donor networks. Further research is needed on how contact evolves over time, particularly regarding early linking (before the legislated age of access in identity-release jurisdictions) and connections made via DNA testing.
Keywords: 1103 Clinical Sciences; 1114 Paediatrics and Reproductive Medicine; Obstetrics & Reproductive Medicine; 3215 Reproductive medicine; donor conception; contact experiences; linking; identity-release